Reverse Logistics as a Sustainable Value Proposition for Product Acquisition. Issue 5 (2nd September 2016) - Darbari, Jyoti Dhingra; Agarwal, Vernika; Jha, P. C.
Abstract: Reverse logistics (RL) is a value proposition that goes beyond just cost reduction and customer satisfaction. It can be used as an efficient tool by manufacturers for overhauling their supply chain performance and also for taking responsibility of the entire life cycle of the product in a sustainable manner. This paper presents a novel model oriented to integrate economic and environmental concerns in the design of RL network for an electronics manufacturing company located in the NCR region of India. A bi-objective mixed integer programming RL model is presented which enables a manufacturer with various recovery options to choose from and decide on an optimal strategy to maximise his profit. Simultaneously, the environmental impact due to transportation activities can be reduced by determining optimal clusters and intra cluster routes and optimal selection of vehicles for backward flow of retrieved products and components. The model seeks to focus on investigating RL practices with a sustainable perspective and can be used as a framework by the company for gaining competitive advantage.